The Influence of Environmental Performance and Board Size on Carbon Emission Disclosure: The Moderating Role of CEO Power in Indonesia's Transportation and Logistics Sector - Agustin, Rita; Pardede, Ratlan (Journal of Social Science, 2024)
The pressing global issue of climate change has led to increased scrutiny over corporate environmental practices, particularly carbon emission disclosures. This research examines the influence of environmental performance and corporate governance mechanisms on the disclosure of carbon emissions within the transportation and logistic sector in Indonesia from 2018 - 2023, with a particular emphasis on the moderating role of CEO Power. Using a quantitative research design, the study incorporates panel data regression analysis to study the impact across various companies listed on the Indonesia Stock Exchange (IDX). The findings reveal that Environmental Performance and Board Size has no effect on Carbon Emission Disclosure. This study contributes to the literature by highlighting the pivotal role of CEO Power in enforcing corporate transparency in environmental performance. It underscores the necessity for stringent governance to bolster ecological accountability. The findings support policymakers and corporate managers in structuring governance frameworks that enhance transparency and encourage sustainable practices